Human Rights in Islamic Perspective - Salamatul Lasmi; Zhang Wei; Shanshan Xu (Yayasan Adra Karima Hubbi, 2023)
Background. The most basic right that Allah SWT has given to mankind is human rights. Purpose The purpose of this is that in the teachings of Islam, the Qur'an and As-Sunnah focus attention on neglected human rights. In fact, with the presence of Islam, one of its goals is to elevate the dignity of mankind and provide teaching with friendly teachings. Method. This type of research is qualitative, namely researchers directly researching tahfiz teachers at the tahfiz house. This research was conducted using qualitative methods, by conducting observations and interviews at the nurul yaqin tahfiz house, namely through ustazah hernita as a teacher at the tahfiz house. Results. Islam came, humans were In the past, before Islam came, humans were treated unnaturally and employed arbitrarily without paying any attention to human values. Conclusion. Therefore, this paper seeks to explain and analyze the nature of human rights from an Islamic perspective with its principles and maqashid al-syari'ah.